Kebiasaan Mengonsumsi Makanan Cepat Saji dan Minuman Bersoda Telah Terbukti Menyebabkan Diabetes Mellitus di Desa Banyuanyar, Banyuwangi - Haswita; Varadila Istika Umami; Rizki Yulia Purwitaningtyas (Journal of Pubnursing Sciences, 2024)
The non-communicable disease with the largest death toll globally is diabetes mellitus (DM). This disease can affect anyone, especially people with risk factors such as obesity, infectious diseases, hereditary factors, or an unhealthy diet. An unhealthy diet can result in increased sugar levels, which leads to serious symptoms such as dehydration, dizziness when standing, shortness of breath, and unconsciousness. This study aims to analyze the relationship between the habit of consuming fast food and soft drinks with the incidence of diabetes mellitus in Banyuanyar village, Banyuwangi. This type of research is of a quantitative type accompanied by a cross sectional design. The population of this study is people with Diabetes Mellitus in Banyuanuar Village, Banyuangi. There were 30 respondents with sample collection using the total sampling methodology. Questionnaires and sugar levels check include research instruments. The results of the Spearman's rho test obtained a significant value of p-value 0.016>0.05, meaning that there was a correlation between the habit of consuming fast food and soft drinks and the incidence of diabetes mellitus in Banyuanyar village, Banyuwangi. The importance of increasing knowledge in consuming fast food and soft drinks.  The conclusion of this study is that there is a significant relationship between the habit of consuming fast food and soft drinks for people with Diabetes Mellitus.